REHABILITATION OF DIZZINESS USING A STABILOMETRIC PLATFORM: A NEUROSCIENTIFIC APPROACH TO VESTIBULAR RECOVERY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Dizziness is a complex clinical condition impairing balance and spatial orientation. This article reviews the use of stabilometric platform therapy in vestibular rehabilitation, highlighting its role in promoting vestibular compensation through sensorimotor integration and neuroplastic adaptation. Clinical evidence demonstrates notable improvements in postural stability and symptom reduction following systematic platform-based training.